Intra-Quranic connections in Sunni and Shi‘i tafsirs: a meeting point or another area of contestation? - Izza Rohman (Indonesian Journal of Islam and Muslim Societies, 2013)
This study seeks to shed light on how a celebrated interpretive approach to theQuran considered to be most objective is taken by interpreters from differenttheological settings. It takes a closer look at how the principle of tafsir al-Qur’anbi al-Qur’an (interpretation of the Quran by the Quran) is employed by al-Shanqitiin his Ad}wa’ al-Bayan and al-Tabataba’i in his al-Mizan, taking their interpretationof ahl al-bayt as a main case in point. Noticing how their differences in this issuecan be associated with their respective Sunni and Shi‘i backgrounds, this studyfinds a number of areas where both modern exegetes – and other exegetes mostlikely – might be influenced by any creeping theological preference in their pur-suit of objectivity and openness to the text.Kajian ini bermaksud menelaah bagaimana sebuah pendekatan penafsiran al-Qur’an yang dianggap paling objektif diterapkan oleh para mufasir dari latarbelakang aliran teologi yang berbeda. Bagaimana prinsip menafsirkan al-Qur’andengan al-Qur’an diaplikasikan oleh al-Shanqiti dalam tafsirnya, Ad}wa’ al-Bayan,dan al-Tabataba’i dalam tafsirnya, al-Mizan, dilihat lebih saksama terutama denganmengambil contoh penafsiran mereka tentang ahlulbait. Mencermati bagaimana perbedaan mereka dalam menafsirkan cakupan ahlul bait bisa dikaitkan denganlatar belakang Sunni dan Syiah mereka, kajian ini menemukan sejumlah ranah dimana kedua mufasir modern ini – dan sepertinya juga mufasir yang lain – bisasaja  dipengaruhi  oleh  kecenderungan  teologis  ketika  mencoba  menjagaobjektivitas dan keterbukaan terhadap teks al-Qur’an.